Major trauma: Does weekend attendance increase 30-day mortality?. Issue 2 (February 2019) - Little, Zoë; Bethel, Jordan; Clements, Jennifer; Trompeter, Alex J.
Highlights: There is no difference in 30-day mortality in major trauma patients attending on weekends compared to weekdays. Mortality is significantly higher in Friday and Saturday attenders which may be explained by greater severity of head injuries. Further research is warranted to investigate the cause of higher mortality rates seen in major trauma patients presenting on a Friday or Saturday. Abstract: Background: Differing mortality rates according to day of hospital admission is an area of debate, where a supposed increased rate of mortality with weekend admissions has been termed "the weekend effect". We sought to identify the 30-day mortality rates in major trauma patients attending our Major Trauma Centre (MTC) and the underlying reasons for these. Methods: A retrospective review of data retrieved from the Trauma Audit and Research Network (TARN) database was undertaken for all patients attending between January 2013 and July 2015 with an Injury Severity Score of 9 or higher. 30-day mortality rates were calculated according to day of attendance. Results: 1424 patients met the inclusion criteria. There was no significant difference in 30-day mortality between weekend attendances (7.8%) compared to those on a weekday (7.7%). 30-day mortality was highest in patients attending on Fridays (10.8%) and lowest in those attending on Sundays (5.5%). A significantly higher 30-day mortality rate was seen in patients attending on a Friday or Saturday (10.4%) compared to those attending Sunday to Thursday (6.6%) (RR 1.548). Patients with a head injury as their most serious injury on a Friday or Saturday were more likely to have GCS < 9 (34.7% vs 24.4%) and more likely to die (22.7% vs 12%) than those attending Sunday to Thursday. Conclusion: There is no significant difference in 30-day mortality when directly comparing weekday to weekend attendances. There is a significantly higher mortality on Friday and Saturday compared to remainder of the week which appears to be explained by a greater severity of head trauma. Implications: This study provides no evidence of a "weekend effect" in this MTC but the increased severity of and mortality from head injury identified on Friday and Saturday is a public health concern which warrants further investigation.